Atmospheric inputs of nutrients to the Mediterranean Sea. (January 2020) - Kanakidou, Maria; Myriokefalitakis, Stelios; Tsagkaraki, Maria
Abstract: The Mediterranean Sea is an oligotrophic semi-closed environment where atmospheric deposition is expected to be an important driver for biological activity. The present study uses a three-dimensional atmospheric chemistry transport model to evaluate the nitrogen (N), phosphorus (P) and iron (Fe) atmospheric deposition fluxes to the Mediterranean Sea. The model takes into account both the inorganic and organic fractions of these fluxes and compares them to other sources of these nutrients that are external to the ocean. The estimated atmospheric deposition fluxes of soluble nutrients amount to 1281 Gg-N y −1, 4.31 Gg-P y −1 and 6.32 Gg-Fe y −1 for the present day, and are within the range of the few estimates available in literature. An almost 6-fold increase in the atmospheric deposition of soluble N is also calculated to be the result of the increase in anthropogenic and biomass burning emissions since 1850, while soluble P and Fe deposition fluxes have increased by 59% and 114%, respectively. For future (2100) emissions, however, N deposition is projected to increase only slightly (4%) while soluble P and Fe fluxes will decrease by 34% and 32% compared to current estimates. The soluble organic N and P annual deposition fluxes are calculated to be 12% and 28–83% of total soluble N and P present-day annual deposition fluxes into the Mediterranean Sea, respectively. However, to reconcile with the observed fluxes in the west and the east Mediterranean, ∼14 times higher flux of soluble P, in particular organic P, and at least 2.5 times higher flux of soluble Fe need to be considered in the model. Such high fluxes can be due to higher combustion emissions of soluble Fe and P, to higher dust emissions or solubilisation of Fe and P contained in dust aerosols, and also higher organic P flux associated with bioaerosols than currently used in the global models. Overall, the calculated deposition fluxes provide an integrated spatially complete picture of the atmospheric inputs to the Mediterranean marine ecosystem, which are potentially important for net primary production and the ocean carbon cycle.